PENGEMBANGAN MODEL PEMBELAJARAN TERPADU BERBASIS BUDAYA UNTUK MENINGKATKAN APRESIASI SISWA TERHADAP BUDAYA LOKAL - Alexon & Nana Syaodih Sukmadinata (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Developing a Culture-Based Integrated Learning Model to ImproveStudents Appreciation of Local Culture. This study aims to develop a social studylearning model for elementary school students that can help them master subjectmatters as an effort to improve their appreciation of local culture, using an R Dapproach consisting of three steps: preliminary study, model development andmodel validation. The subjects were teachers and students of elementary schools inBengkulu Province, Sumatra. The results show that the Culture-Based IntegratedLearning Model (CBILM) is an appropriate learning model to help students mastersubject matters as an effort to improve their appreciation of local culture. CBILM ismore capable of significantly improving students appreciation of local culture andtheir mastery of subject matters than the currently existing learning model.Keywords: learning model, social studies for elementary schools, cultureappreciation